A Zone-II Flexor Tendon Injury Secondary to a Catfish Spine: A Case Report. Issue 3 (July 2017) - Spitler, Clay; Rehm, Jason
Abstract : Case: We present the case of a 17-year-old man who sustained a delayed rupture of a zone-II flexor tendon injury in the long finger from a catfish spine, which caused local envenomization and a likely secondary bacterial infection. He underwent surgical exploration and irrigation and debridement of the finger. The flexor digitorum profundus tendon was found to be lacerated and was primarily repaired. Conclusion: Catfish spines can cause traumatic disruption of anatomic structures and can envenomate the area of injury, which can lead to a secondary bacterial infection. We review the literature regarding catfish spine injuries and describe a basic treatment algorithm for patients who are injured by catfish spines.